Pelatihan Digitalisasi Pertanian untuk Meningkatkan Efisiensi Usaha Agribisnis di Wilayah Katibung - Ihsan Mustofa; Subandi; Nurleni Wahyuningsih (Wisanggeni: Jurnal Pengabdian Masyarakat, 2021)
The growth of the agribusiness sector in Indonesia is challenged by production and distribution efficiency due to low adoption of digital technology. In the Katibung area, South Lampung Regency, small-medium scale agribusiness actors face limited knowledge and access to agricultural digital technology. This community service aims to improve the efficiency of agribusiness businesses through agricultural digitalization training, targeting agribusiness actors and local farmers. The methods used include interactive training, technical assistance, and questionnaire-based evaluation. The results showed an increase in participants' understanding and skills in the use of land management applications, digital marketing, and Internet of Things (IoT)-based production monitoring. The implications of this activity are increased productivity, operational cost efficiency, and expanded market access through digital platforms.